(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2014)
The latest open commercial markets among countries, shift of capitals, and rise of mass economic, large international organizations, and international contracts leaded to a great increase of competition among countries for attracting capital for investments, specially among under developing countries which had bad economic situation, and which thinks that investment is the best solution to solve their old economic problems. Developing small, and medium establishments in all economic sectors became the main economic force and natural resources for the development and growth of under developing countries. Small and medium establishments became the majority of any country establishments, and the past international experience shows that most of the developed, and under developing countries seek all ways to increase the number of small, and medium establishments. It is believed that those kind of establishments are too important because of the main roll they play in fulfilling the resources, increasing the added value, and achieving vertical accumulation required in any economy. This research will deal with the concept of foreign investments, its nature, types, environmental elements, and by taking a close look at Jordanian experience in this matter for the period between 1970 and 2004, in away to point out the main elements and variables that encourage attracting foreign investments to this.